SEMICONDUCTOR NANOPARTICLE COMPOSITE, SEMICONDUCTOR NANOPARTICLE COMPOSITE COMPOSITION, AND SEMICONDUCTOR NANOPARTICLE COMPOSITE CURED FILM
The semiconductor nanoparticle composite with dual ligands addresses the issues of low efficiency and heat resistance by strengthening bonding, ensuring high performance in diverse applications.
Patent Information
- Application Number
- JP2021521904
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2019-05-31
- Filing Date
- 2020-05-29
- Publication Date
- 2024-12-18
- Estimated Expiration
- 2040-05-29
AI Technical Summary
Semiconductor nanoparticles face issues with low fluorescence quantum efficiency and poor heat resistance due to weak ligand bonding, leading to decreased performance in applications requiring high temperatures and various dispersion media.
A semiconductor nanoparticle composite is developed with two types of ligands, Ligand I having one mercapto group and Ligand II having at least two mercapto groups, coordinated to the surface of the nanoparticles, enhancing bonding strength and stability.
The composite exhibits improved fluorescence quantum efficiency and heat resistance, allowing for efficient dispersion in various media and maintaining performance under high temperatures.
Smart Images

Figure 0007602207000001 
Figure 0007602207000002 
Figure 0007602207000003
Abstract
Description
[Technical field]
[0001] The present invention relates to a semiconductor nanoparticle composite, a semiconductor nanoparticle composite composition, a semiconductor nanoparticle composite cured film, a semiconductor nanoparticle composite dispersion, a method for producing a semiconductor nanoparticle composite composition, and a method for producing a semiconductor nanoparticle composite cured film. This application claims priority to Japanese Patent Application No. 2019-103241 filed on May 31, 2019, and Japanese Patent Application No. 2019-103242 filed on the same day, and incorporates by reference all of the contents of said Japanese Patent Application. [Background technology]
[0002] Semiconductor nanoparticles that are small enough to exhibit the quantum confinement effect have a band gap that depends on the particle size. Excitons formed in the semiconductor nanoparticles by means of photoexcitation, charge injection, etc. recombine to emit photons with energy corresponding to the band gap, so that light emission at a desired wavelength can be obtained by appropriately selecting the composition of the semiconductor nanoparticles and their particle size.
[0003] In the early stages of research into semiconductor nanoparticles, the focus was on elements containing Cd and Pb. However, because Cd and Pb are subject to restrictions such as the Restriction of the Use of Certain Hazardous Substances, research has been focused in recent years on non-Cd- and non-Pb-based semiconductor nanoparticles.
[0004] Attempts have been made to apply semiconductor nanoparticles to various applications, such as displays, biological labeling, and solar cells. In particular, for display applications, semiconductor nanoparticles have begun to be made into films and used as wavelength conversion layers. [Prior art documents] [Patent documents]
[0005] [Patent Document 1] JP 2013-136498 A [Patent Document 2] International Publication No. 2017 / 038487 [Non-patent literature]
[0006] [Non-Patent Document 1] Takashi Jin, "Semiconductor Quantum Dots, Their Synthesis and Applications to Life Sciences," Production and Technology, Vol. 63, No. 2, pp. 58-63, 2011 [Non-Patent Document 2] Fabien Dubois et al, “A Versatile Strategy for Quantum Dot Ligand Exchange” J.AM.CHEM.SOC Vol.129, No.3, p.482-483, 2007 [Non-Patent Document 3] Boon-Kin Pong et al, “Modified Ligand-Exchange for Efficient Solubilization of CdSe / ZnS Quantum Dots in Water: A Procedure Guided by Computational Studies” Langmuir Vol.24, No.10, p.5270-5276, 2008 [Non-Patent Document 4] Samsulida Abd. Rahman et al, “Thiolate-Capped CdSe / ZnS Core-Shell Quantum Dots for the Sensitive Detection of Glucose” Sensors Vol.17, No.7, p.1537, 2017 [Non-Patent Document 5] Whitney Nowak Wenger et al, “Functionalization of Cadmium Selenide Quantum Dots with Poly(ethylene glycol): Ligand Exchange, Surface Coverage, and Dispersion Stability” Langmuir, Vol.33, No.33, pp8239-8245, 2017 Summary of the Invention [Problem to be solved by the invention]
[0007] Semiconductor nanoparticles are generally dispersed in a dispersion medium to prepare a semiconductor nanoparticle dispersion liquid, which is then applied in various fields. When semiconductor nanoparticles are used alone, the dispersion media in which they can be dispersed are limited depending on the surface condition of the semiconductor nanoparticles. Therefore, by coordinating ligands to the surface of the semiconductor nanoparticles, it becomes possible to disperse the semiconductor nanoparticles in the dispersion media required for application in each field.
[0008] Non-Patent Documents 1 to 5 and Patent Document 1 disclose that the dispersion medium in which the semiconductor nanoparticles can be dispersed can be changed by replacing the ligands coordinated to the surface of the semiconductor nanoparticles with different ligands. Furthermore, Patent Document 2 discloses a semiconductor nanoparticle composite that uses a ligand having a carboxyl group and a ligand having a mercapto group and coordinates both ligands to the surface of a semiconductor nanoparticle, and has high fluorescence quantum efficiency and good luminescence stability against ultraviolet light and the like.
[0009] In semiconductor nanoparticle composites, the binding strength between the semiconductor nanoparticles and the ligand varies depending on the type of coordinating group of the ligand. If a ligand with weak binding strength is coordinated to a semiconductor nanoparticle, the ligand with weak binding strength to the semiconductor nanoparticle will be released from the semiconductor nanoparticle when the semiconductor nanoparticle composite is dispersed in a dispersion medium, resulting in a decrease in fluorescence quantum efficiency.
[0010] Furthermore, depending on the application, the semiconductor nanoparticle composite may be exposed to high temperatures of about 200° C. in the presence of oxygen during processes such as the step of forming the semiconductor nanoparticle composite into a film, the step of baking a photoresist containing the semiconductor nanoparticle composite, or the step of removing the solvent and curing the resin after inkjet patterning of the semiconductor nanoparticle composite. In such cases, the ligands that have a weak binding strength with the semiconductor nanoparticles as described above are more likely to be detached from the surface of the semiconductor nanoparticles, resulting in a decrease in the fluorescence quantum efficiency.
[0011] The present inventors have studied the semiconductor nanoparticle composite described in Patent Document 2 with the aim of improving the fluorescence quantum efficiency of the semiconductor nanoparticle composite and improving the stability of the fluorescence quantum efficiency when exposed to high temperatures (hereinafter referred to as "heat resistance" in this application), and have found that the semiconductor nanoparticle composite has poor heat resistance.
[0012] Therefore, an object of the present invention is to provide a semiconductor nanoparticle composite that has both improved fluorescent quantum efficiency and improved heat resistance. [Means for solving the problem]
[0013] The semiconductor nanoparticle composite according to the present invention is A semiconductor nanoparticle composite in which two or more ligands including ligand I and ligand II are coordinated to the surface of a semiconductor nanoparticle, The ligand comprises an organic group and a coordinating group, The ligand I has one mercapto group as the coordinating group, The ligand II has at least two mercapto groups as the coordinating groups. A semiconductor nanoparticle composite. In this application, the range indicated by "~" is the range including the numbers on both ends. Effect of the Invention
[0014] According to the present invention, it is possible to provide a semiconductor nanoparticle composite that has both improved fluorescent quantum efficiency and improved heat resistance. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0015] In order to achieve the above object, the present inventors have conducted intensive research and found that by appropriately selecting the type of ligand, a semiconductor nanoparticle composite having high fluorescence quantum efficiency and high heat resistance can be obtained, and further found that a dispersion containing a high mass fraction of the semiconductor nanoparticle composite can be obtained. That is, one aspect of the present invention relates to a semiconductor nanoparticle composite consisting of semiconductor nanoparticles and a ligand coordinated to the surface of the semiconductor nanoparticles, as well as a semiconductor nanoparticle composite composition and a semiconductor nanoparticle composite cured film containing the semiconductor nanoparticle composite. Another aspect of the present invention relates to a semiconductor nanoparticle composite dispersion in which a semiconductor nanoparticle composite consisting of semiconductor nanoparticles and a ligand coordinated to the surface of the semiconductor nanoparticles is dispersed in a dispersion medium, as well as a method for producing a semiconductor nanoparticle composite composition and a method for producing a semiconductor nanoparticle composite cured film using the semiconductor nanoparticle composite dispersion.
[0016] In the present invention, the semiconductor nanoparticle composite is a semiconductor nanoparticle composite having light emitting properties. The semiconductor nanoparticle composite of the present invention is a particle that absorbs light of 340 nm to 480 nm and emits light with an emission peak wavelength of 400 nm to 750 nm. The full width at half maximum (FWHM) of the emission spectrum of the semiconductor nanoparticle composite is preferably 40 nm or less, more preferably 38 nm or less, and further preferably 35 nm or less, for reasons such as preventing color mixing when the semiconductor nanoparticle composite is applied to a display or the like.
[0017] The semiconductor nanoparticle composite preferably has a fluorescence quantum efficiency (QY) of 70% or more. Since a fluorescence quantum efficiency of 70% or more allows for more efficient color conversion, the fluorescence quantum efficiency is more preferably 75% or more, and further preferably 80% or more. In the present invention, the fluorescence quantum efficiency of the semiconductor nanoparticle composite can be measured using a quantum efficiency measurement system.
[0018] -Semiconductor nanoparticles- The semiconductor nanoparticles constituting the semiconductor nanoparticle composite are not particularly limited as long as they satisfy the above-mentioned luminescence characteristics such as the fluorescence quantum efficiency and the half-width, and may be particles made of one type of semiconductor or particles made of two or more different types of semiconductors. In the case of particles made of two or more different types of semiconductors, the semiconductors may form a core-shell structure. For example, the particles may be core-shell type particles having a core containing a group III element and a group V element and a shell containing group II and group VI elements that covers at least a part of the core. Here, the shell may have a plurality of shells made of different compositions, and may have one or more gradient shells in which the ratio of the elements constituting the shell changes in the shell.
[0019] Specific examples of Group III elements include In, Al, and Ga. Specific examples of Group V elements include P, N and As. The composition for forming the core is not particularly limited, but InP is preferable from the viewpoint of light emission characteristics.
[0020] The Group II element is not particularly limited, but examples thereof include Zn and Mg. Group VI elements include, for example, S, Se, Te and O. The composition forming the shell is not particularly limited, but from the viewpoint of the quantum confinement effect, ZnS, ZnSe, ZnSeS, ZnTeS, ZnTeSe, etc. are preferable. In particular, when Zn element is present on the surface of the semiconductor nanoparticle, the effect of the present invention can be more effectively exhibited.
[0021] In the case where there are multiple shells, it is sufficient that at least one shell of the above-mentioned composition is included. In addition, in the case where there is a gradient type shell in which the ratio of the elements constituting the shell changes within the shell, the shell does not necessarily have to have the composition as indicated in the composition notation. Here, in the present invention, whether the shell covers at least a portion of the core and the element distribution inside the shell can be confirmed by, for example, composition analysis using energy dispersive X-ray spectroscopy with a transmission electron microscope (TEM-EDX).
[0022] The average particle size of the semiconductor nanoparticles is preferably 10 nm or less, and more preferably 7 nm or less. In the present invention, the average particle size of the semiconductor nanoparticles can be measured by calculating the particle sizes of 10 or more particles in a particle image observed using a transmission electron microscope (TEM) as the equivalent circle diameter (Heywood diameter). From the viewpoint of luminescence characteristics, it is preferable that the particle size distribution is narrow, and the coefficient of variation is preferably 15% or less. Here, the coefficient of variation is defined as "coefficient of variation = standard deviation of particle size / average particle size". A coefficient of variation of 15% or less is an indicator that semiconductor nanoparticles with a narrower particle size distribution have been obtained.
[0023] -Ligand- In the present invention, the semiconductor nanoparticle composite is a semiconductor nanoparticle having a ligand coordinated to the surface thereof. The term "coordination" used herein means that the ligand chemically affects the surface of the semiconductor nanoparticle. The ligand may be bonded to the surface of the semiconductor nanoparticle by a coordinate bond or any other bonding mode (e.g., a covalent bond, an ionic bond, a hydrogen bond, etc.), or may not necessarily be bonded when at least a portion of the surface of the semiconductor nanoparticle has a ligand.
[0024] In the present invention, the ligand comprises a coordinating group that coordinates with the semiconductor nanoparticles and an organic group. At least one of the ligands that coordinate to the semiconductor nanoparticles to form a semiconductor nanoparticle composite is Ligand I, which has one mercapto group as a coordinating group, and at least one of the ligands is Ligand II, which has at least two mercapto groups as coordinating groups.
[0025] The mercapto groups of ligands I and II are strongly coordinated to the shell of the semiconductor nanoparticles, filling in the defects of the semiconductor nanoparticles, preventing a decrease in the luminescence properties of the semiconductor nanoparticles, and contributing to improving the heat resistance. When Zn is present on the surface of the semiconductor nanoparticles, the above-mentioned effects are more pronounced due to the strength of the bond between the mercapto groups and Zn. The organic group of the ligand I is preferably a monovalent hydrocarbon group which may have a substituent or a hetero group. This structure allows dispersion in various dispersion media compared to the case where an inorganic ligand is coordinated.
[0026] Although not particularly limited, the ligand I is preferably an alkylthiol. In particular, from the viewpoint of heat resistance, an alkylthiol having an alkyl group having 6 to 14 carbon atoms is preferable, and further, hexanethiol, octanethiol, decanethiol, or dodecanethiol is preferable.
[0027] The organic group of the ligand II is preferably a divalent or higher hydrocarbon group which may have a substituent or a hetero group. This structure improves the dispersibility in a dispersion medium, enables dispersion in various dispersion media, and further improves heat resistance. Each mercapto group of the ligand II is preferably present via five or fewer carbon atoms, and more preferably via three or fewer carbon atoms from the viewpoint of preventing crosslinking reactions between semiconductor nanoparticles.
[0028] Since the ligand II has at least two or more mercapto groups, one molecule of the ligand II can be strongly coordinated to multiple locations on the surface of the semiconductor nanoparticle. However, this can cause a decrease in the density of the ligand near the surface of the semiconductor nanoparticle, which can lead to a decrease in heat resistance. In the semiconductor nanoparticle composite of the present invention, by also coordinating the ligand I, it is possible to prevent a decrease in the density of the ligand near the surface of the semiconductor nanoparticle and increase the heat resistance.
[0029] Since the ligand II has at least two or more mercapto groups, one molecule of the ligand II can be firmly coordinated to multiple locations on the surface of the semiconductor nanoparticle. As a result, the heat resistance of the semiconductor nanoparticle composite is improved. Furthermore, the amount of the ligand in the semiconductor nanoparticle composite is reduced compared to a monovalent ligand, and the semiconductor nanoparticle composite can be dispersed at a high mass fraction in the dispersion medium. However, the density of the ligand near the surface of the semiconductor nanoparticle decreases, which can cause a decrease in heat resistance. Therefore, by coordinating the ligand I together, it is possible to prevent a decrease in the density of the ligand near the surface of the semiconductor nanoparticle and increase the heat resistance. In addition, by coordinating the ligand I and the ligand II together, the semiconductor nanoparticle composite can not only adjust the dispersibility, but also disperse at a high mass fraction in the dispersion medium. The mass ratio of ligand I to ligand II (ligand I / ligand II) is preferably 0.2 to 1.5, and more preferably 0.3 to 1.0 from the viewpoints of improving heat resistance and adjusting dispersibility described above.
[0030] In the semiconductor nanoparticle composite, the mass ratio of the ligand to the semiconductor nanoparticles (ligand / semiconductor nanoparticles) is preferably 0.05 or more and 0.60 or less. By being 0.05 or more, the surface of the semiconductor nanoparticles can be sufficiently covered with the ligand, the luminescence properties of the semiconductor nanoparticles are not reduced, and the dispersibility in a dispersion, a composition, or a cured film can be improved. In addition, by being 0.60 or less, the size and volume of the semiconductor nanoparticle composite can be suppressed from increasing, and it becomes easy to increase the mass fraction when dispersed in a dispersion, a composition, or a cured film. In addition, in the semiconductor nanoparticle composite, the mass ratio of the ligand to the semiconductor nanoparticles (ligand / semiconductor nanoparticles) is more preferably 0.15 or more and 0.35 or less.
[0031] The molecular weight of each of the ligands is preferably 50 or more and 600 or less, and more preferably 450 or less. By making the molecular weight of the ligand 50 or more, the surface of the semiconductor nanoparticles can be sufficiently covered with the ligand, the luminescence properties of the semiconductor nanoparticles are not reduced, and the dispersibility in a dispersion, a composition, or a cured film can be increased. In addition, by making the molecular weight of the ligand 600 or less, the size and volume of the semiconductor nanoparticle composite are prevented from increasing, and it becomes easy to increase the mass fraction when dispersed in a dispersion, a composition, or a cured film.
[0032] Ligands other than Ligand I and Ligand II may be coordinated to the surface of the semiconductor nanoparticles. When ligands other than Ligand I and Ligand II are coordinated, the total mass fraction of Ligand I and Ligand II with respect to all the ligands is preferably 0.7 or more. By being in this range, as described above, it is possible to improve heat resistance while enabling adjustment of dispersibility. Furthermore, when a ligand other than ligand I and ligand II is coordinated to the surface of the semiconductor nanoparticle, the molecular weight of the ligand other than ligand I and ligand II is preferably 50 or more and 600 or less, and more preferably 450 or less.
[0033] (Method of Producing Semiconductor Nanoparticle Composite) -Method of manufacturing semiconductor nanoparticles- An example of a method for producing semiconductor nanoparticles will be disclosed below. The cores of the semiconductor nanoparticles can be formed by mixing a Group III precursor, a Group V precursor, and, if necessary, an additive in a solvent and heating the resulting precursor mixture. Solvents include, but are not limited to, 1-octadecene, hexadecane, squalane, oleylamine, trioctylphosphine, trioctylphosphine oxide, and the like. Group III precursors include, but are not limited to, acetates, carboxylates, and halides containing the Group III elements. Group V precursors include, but are not limited to, organic compounds and gases containing the group V elements. When the precursor is a gas, the core can be formed by injecting the gas into a precursor mixture containing other gases and reacting them.
[0034] The semiconductor nanoparticles may contain one or more elements other than Group III and Group V elements, as long as the effects of the present invention are not impaired. In such cases, precursors of the elements can be added during core formation. Examples of additives include dispersants such as carboxylic acids, amines, thiols, phosphines, phosphine oxides, phosphinic acids, and phosphonic acids, but are not limited thereto. The dispersant can also serve as a solvent. After the core of the semiconductor nanoparticle is formed, a halide can be added as necessary to improve the light emitting properties of the semiconductor nanoparticle.
[0035] In one embodiment, a metal precursor solution in which an In precursor and, if necessary, a dispersant are added to a solvent is mixed under vacuum, and the mixture is heated at 100°C to 300°C for 6 to 24 hours, after which a P precursor is added and the mixture is heated at 200°C to 400°C for 3 to 60 minutes, and then cooled. A halogen precursor is further added and the mixture is heated at 25°C to 300°C, preferably 100°C to 300°C, more preferably 150°C to 280°C, to obtain a core particle dispersion liquid containing core particles.
[0036] By adding a shell-forming precursor to the synthesized core particle dispersion, the semiconductor nanoparticles can adopt a core-shell structure, thereby improving the quantum efficiency (QY) and stability. The elements that make up the shell are thought to form an alloy, heterostructure, or amorphous structure on the surface of the core particle, but it is also possible that some of them migrate to the inside of the core particle by diffusion.
[0037] The added shell-forming element is mainly present near the surface of the core particle and plays a role in protecting the semiconductor nanoparticle from external factors. In the core-shell structure of the semiconductor nanoparticle, the shell preferably covers at least a part of the core, and more preferably uniformly covers the entire surface of the core particle.
[0038] In one embodiment, a Zn precursor and a Se precursor are added to the aforementioned core particle dispersion liquid, and then the mixture is heated at 150° C. to 300° C., and more preferably at 180° C. to 250° C., and then a Zn precursor and a S precursor are added, and the mixture is heated at 200° C. to 400° C., and preferably at 250° C. to 350° C. This allows core-shell type semiconductor nanoparticles to be obtained. Here, although not particularly limited, examples of Zn precursors that can be used include carboxylates such as zinc acetate, zinc propionate, and zinc myristate, halides such as zinc chloride and zinc bromide, and organic salts such as diethylzinc. As the Se precursor, phosphine selenides such as tributylphosphine selenide, trioctylphosphine selenide, and tris(trimethylsilyl)phosphine selenide, selenols such as benzeneselenol and selenocysteine, and selenium / octadecene solutions can be used. As the S precursor, phosphine sulfides such as tributylphosphine sulfide, trioctylphosphine sulfide, and tris(trimethylsilyl)phosphine sulfide, thiols such as octanethiol, dodecanethiol, and octadecanethiol, and sulfur / octadecene solution can be used. The shell precursors may be mixed in advance and added all at once or in multiple portions, or each may be added separately all at once or in multiple portions. When the shell precursors are added in multiple portions, each addition may be heated at a different temperature.
[0039] In the present invention, the method for producing semiconductor nanoparticles is not particularly limited, and in addition to the methods described above, any method may be used, including conventional production methods such as the hot injection method, the homogeneous solvent method, the reverse micelle method, and the CVD method.
[0040] -Method of manufacturing semiconductor nanoparticle composite- The semiconductor nanoparticle composite can be produced by coordinating the above-mentioned ligand to the semiconductor nanoparticle produced as described above. There is no limitation on the method of coordinating the ligand to the semiconductor nanoparticles, but a ligand exchange method utilizing the coordination power of the ligand can be used. Specifically, the semiconductor nanoparticles in which the organic compound used in the process of producing the semiconductor nanoparticles is coordinated to the surface of the semiconductor nanoparticles are contacted with the target ligand in a liquid phase to obtain a semiconductor nanoparticle composite in which the target ligand is coordinated to the surface of the semiconductor nanoparticles. In this case, a liquid phase reaction using a solvent as described below is usually performed, but if the ligand used is liquid under the reaction conditions, it is also possible to use the ligand itself as the solvent and to adopt a reaction format in which no other solvent is added.
[0041] Furthermore, if a purification step and a redispersion step as described below are carried out before the ligand exchange, the ligand exchange can be easily carried out. As another method, a ligand may be added to the precursor for forming the semiconductor nanoparticles and reacted. When the semiconductor nanoparticles have a core-shell structure, the ligand may be added to either the core precursor or the shell precursor.
[0042] In one embodiment, the semiconductor nanoparticle-containing dispersion liquid after the production of the semiconductor nanoparticles is purified and redispersed, and then a solvent containing ligand I and ligand II is added and stirred at 50°C to 200°C for 1 to 120 minutes in a nitrogen atmosphere to obtain the desired semiconductor nanoparticle composite.
[0043] The semiconductor nanoparticle composites can be purified as follows. In one embodiment, the semiconductor nanoparticle composites can be precipitated from the dispersion by adding a polarity-reversing solvent such as acetone. The precipitated semiconductor nanoparticle composites can be collected by filtration or centrifugation, while the supernatant containing unreacted starting materials and other impurities can be discarded or reused. The precipitated semiconductor nanoparticle composites can then be washed with additional dispersion medium and dispersed again. This purification process can be repeated, for example, 2-4 times, or until the desired purity is reached.
[0044] In the present invention, the method for purifying the semiconductor nanoparticle composite is not particularly limited, and in addition to the methods described above, for example, coagulation, liquid-liquid extraction, distillation, electrodeposition, size exclusion chromatography and / or ultrafiltration, or any other method can be used alone or in combination. These purification methods can also be used prior to the above-mentioned ligand exchange in order to facilitate the ligand exchange of semiconductor nanoparticles.
[0045] The ligand composition in the semiconductor nanoparticle complex can be quantified using 1H-NMR. The obtained semiconductor nanoparticles are dispersed in a deuterated solvent, and electromagnetic waves are applied in a magnetic field to cause 1H nuclear magnetic resonance. The free induction decay signal obtained at this time is subjected to Fourier analysis to obtain a 1H-NMR spectrum. The 1H-NMR spectrum gives characteristic signals at positions corresponding to the structure of the ligand species. The composition of the target ligand is calculated from the positions of these signals and the integrated intensity ratio. Examples of deuterated solvents include CDCl3, acetone-d6, and N-hexane-D14.
[0046] The optical properties of the semiconductor nanoparticle composite can be measured using a fluorescence quantum efficiency measurement system (e.g., QE-2100, manufactured by Otsuka Electronics). The obtained semiconductor nanoparticle composite is dispersed in a dispersion liquid, and an emission spectrum is obtained by applying excitation light. From the emission spectrum obtained here, the fluorescence quantum efficiency (QY) and the full width at half maximum (FWHM) are calculated from the emission spectrum after re-excitation correction, which is obtained by removing the re-excitation fluorescence emission spectrum of the fluorescence emitted by re-excitation. Examples of the dispersion liquid include normal hexane, toluene, acetone, PGMEA, and octadecene.
[0047] The heat resistance of the semiconductor nanoparticle composite is evaluated using a dry powder. The dispersion medium is removed from the purified semiconductor nanoparticle composite, and the dry powder is heated in air at 180°C for 5 hours. After the heat treatment, the semiconductor nanoparticle composite is redispersed in a dispersion liquid, and the re-excitation corrected fluorescence quantum efficiency (=QYb) is measured. If the fluorescence quantum efficiency before heating is "QYa", the rate of change in fluorescence quantum efficiency before and after heat treatment can be calculated using the following (Equation 1). (Formula 1): {1-(QYb / QYa)}×100 The heat resistance can be calculated by the following formula (2). (Formula 2): (QYb / QYa)×100 In other words, a change rate of less than 10% between the fluorescence quantum efficiency before and after heating indicates that the heat resistance is 90% or higher. The heat resistance of 90% or more can suppress a decrease in fluorescence quantum efficiency even after the semiconductor nanoparticle composite is subjected to processes such as a film-forming process, a baking process for a photoresist containing semiconductor nanoparticles, or a solvent removal and resin curing process after inkjet patterning of semiconductor nanoparticles.
[0048] (Semiconductor nanoparticle composite dispersion) The semiconductor nanoparticle composite contained in the semiconductor nanoparticle composite dispersion of the present invention can adopt the configuration of the semiconductor nanoparticle composite of the present invention described above. In the present invention, the state in which the semiconductor nanoparticle composite is dispersed in a dispersion medium refers to a state in which the semiconductor nanoparticle composite does not precipitate or does not remain as visible turbidity (cloudiness) when the semiconductor nanoparticle composite and the dispersion medium are mixed. Note that the semiconductor nanoparticle composite dispersed in the dispersion medium is referred to as a semiconductor nanoparticle composite dispersion.
[0049] By setting the mass ratio of ligand I to ligand II to the aforementioned ratio, it becomes possible to disperse the semiconductor nanoparticle composite in at least one of the dispersion media selected from hexane, acetone, propylene glycol monomethyl ether acetate (PGMEA), propylene glycol monomethyl ether (PGME), isobornyl acrylate (IBOA), ethanol, methanol, and mixtures of any combination of these groups, so that the mass fraction of the semiconductor nanoparticles is 20 mass% or more. By dispersing in these dispersion media, the semiconductor nanoparticle composite can be used while maintaining its dispersibility when applied to dispersion in cured films and resins, which will be described later. In the semiconductor nanoparticle composite dispersion of the present invention in which the semiconductor nanoparticle composite of the present invention is dispersed, the semiconductor nanoparticle composite is dispersed at a high mass fraction, and as a result, the mass fraction of the semiconductor nanoparticles in the semiconductor nanoparticle composite dispersion can be made 20 mass% or more, further 25 mass% or more, further 30 mass% or more, and even 35 mass% or more.
[0050] (Semiconductor nanoparticle composite composition) In the present invention, a monomer or a prepolymer can be selected as the dispersion medium of the semiconductor nanoparticle composite dispersion to form a semiconductor nanoparticle composite composition. The monomer or prepolymer is not particularly limited, but examples thereof include radical polymerizable compounds containing an ethylenically unsaturated bond, siloxane compounds, epoxy compounds, isocyanate compounds, and phenol derivatives. Acrylic monomers are preferred from the viewpoint of being able to widely select the application destinations of the semiconductor nanoparticle composite. In particular, examples of acrylic monomers include lauryl acrylate, isodecyl acrylate, stearyl acrylate, isobornyl acrylate, 3,5,5-trimethylcyclohexanol acrylate, 1,6-hexadiol diacrylate, cyclohexadimethanol diacrylate, tricyclodecane dimethanol diacrylate, polyethylene glycol diacrylate, trimethylolpropane triacrylate, tris(2-hydroxyethyl)isocyanurate triacrylate, pentaerythritol tetraacrylate, ditrimethylolpropane acrylate, and dipentaerythritol hexaacrylate, depending on the application of the semiconductor nanoparticle composite. Furthermore, a crosslinking agent may be added to the semiconductor nanoparticle composite composition. The crosslinking agent is selected from polyfunctional (meth)acrylates, polyfunctional silane compounds, polyfunctional amines, polyfunctional carboxylic acids, polyfunctional thiols, polyfunctional alcohols, polyfunctional isocyanates, and the like, depending on the type of monomer in the semiconductor nanoparticle composite composition. Furthermore, the semiconductor nanoparticle composite composition may further contain various organic solvents that do not affect curing, such as aliphatic hydrocarbons such as pentane, hexane, cyclohexane, isohexane, heptane, octane, and petroleum ether, alcohols, ketones, esters, glycol ethers, glycol ether esters, aromatic hydrocarbons such as benzene, toluene, xylene, and mineral spirits, and alkyl halides such as dichloromethane and chloroform. The above organic solvents can be used not only for diluting the semiconductor nanoparticle composite composition, but also as a dispersion medium. That is, it is also possible to disperse the semiconductor nanoparticle composite of the present invention in the above organic solvent to obtain a semiconductor nanoparticle composite dispersion.
[0051] Furthermore, the semiconductor nanoparticle composite composition may contain appropriate initiators, scattering agents, catalysts, binders, surfactants, adhesion promoters, antioxidants, ultraviolet absorbers, anti-aggregation agents, dispersants, and the like, depending on the type of monomer in the semiconductor nanoparticle composite composition. Furthermore, in order to improve the optical properties of the semiconductor nanoparticle composite composition or the semiconductor nanoparticle composite cured film described later, the semiconductor nanoparticle composite composition may contain a scattering agent. The scattering agent is a metal oxide such as titanium oxide or zinc oxide, and the particle size thereof is preferably 100 nm to 500 nm. From the viewpoint of the scattering effect, the particle size of the scattering agent is more preferably 200 nm to 400 nm. The inclusion of a scattering agent increases the absorbance by about two times. The content of the scattering agent is preferably 2 mass % to 30 mass % relative to the composition, and more preferably 5 mass % to 20 mass % from the viewpoint of maintaining the patternability of the composition.
[0052] The semiconductor nanoparticle composite of the present invention allows the semiconductor nanoparticle composite content in the semiconductor nanoparticle composite composition to be 20% by mass or more. By setting the mass fraction of the semiconductor nanoparticles in the semiconductor nanoparticle composite composition to 30% by mass to 95% by mass, the semiconductor nanoparticle composite and the semiconductor nanoparticles can be dispersed at a high mass fraction in the cured film described below.
[0053] When the semiconductor nanoparticle composite composition of the present invention is formed into a 10 μm film, the absorbance of the film with respect to light having a wavelength of 450 nm from the normal direction is preferably 1.0 or more, more preferably 1.3 or more, and even more preferably 1.5 or more. This allows efficient absorption of light from a backlight, thereby making it possible to reduce the thickness of the cured film described below and to miniaturize the device to which it is applied.
[0054] (Diluted Composition) The diluted composition is obtained by diluting the aforementioned semiconductor nanoparticle composite composition of the present invention with an organic solvent. The organic solvent for diluting the semiconductor nanoparticle composite composition is not particularly limited, and examples thereof include aliphatic hydrocarbons such as pentane, hexane, cyclohexane, isohexane, heptane, octane, and petroleum ether, alcohols, ketones, esters, glycol ethers, glycol ether esters, aromatic hydrocarbons such as benzene, toluene, xylene, and mineral spirits, and alkyl halides such as dichloromethane and chloroform. Among these, glycol ethers and glycol ether esters are preferred from the viewpoints of solubility in a wide range of resins and uniformity of the coating when applied.
[0055] (Cured film of semiconductor nanoparticle composite) In the present invention, the term "semiconductor nanoparticle composite cured film" refers to a film containing a semiconductor nanoparticle composite and being cured. The semiconductor nanoparticle composite cured film can be obtained by curing the above-mentioned semiconductor nanoparticle composite composition or diluted composition into a film. The semiconductor nanoparticle composite cured film contains semiconductor nanoparticles, ligands coordinated to the surfaces of the semiconductor nanoparticles, and a polymer matrix. The polymer matrix is not particularly limited, and examples thereof include (meth)acrylic resin, silicone resin, epoxy resin, silicone resin, maleic acid resin, butyral resin, polyester resin, melamine resin, phenolic resin, polyurethane resin, etc. The semiconductor nanoparticle composite cured film may be obtained by curing the above-mentioned semiconductor nanoparticle composite composition. The semiconductor nanoparticle composite cured film may further contain a crosslinking agent.
[0056] The method for curing the film is not particularly limited, and the film can be cured by a curing method suitable for the composition constituting the film, such as heat treatment or ultraviolet treatment. The semiconductor nanoparticles contained in the semiconductor nanoparticle composite cured film and the ligands coordinated to the surface of the semiconductor nanoparticles preferably constitute the semiconductor nanoparticle composite described above. By configuring the semiconductor nanoparticle composite contained in the semiconductor nanoparticle composite cured film of the present invention as described above, it is possible to disperse the semiconductor nanoparticle composite in the cured film at a higher mass fraction. As a result, the mass fraction of the semiconductor nanoparticles in the semiconductor nanoparticle composite cured film can be 20 mass% or more, and even 40 mass% or more. However, if it is 70 mass% or more, the composition constituting the film becomes less, making it difficult to cure and form the film.
[0057] The semiconductor nanoparticle composite cured film of the present invention contains a high mass fraction of the semiconductor nanoparticle composite, and therefore the absorbance of the semiconductor nanoparticle composite cured film can be increased. When the semiconductor nanoparticle composite cured film has a thickness of 10 μm, the absorbance of the semiconductor nanoparticle composite cured film is preferably 1.0 or more, more preferably 1.3 or more, and even more preferably 1.5 or more, relative to light having a wavelength of 450 nm from the normal direction of the semiconductor nanoparticle composite cured film.
[0058] Furthermore, since the semiconductor nanoparticle composite cured film of the present invention contains a semiconductor nanoparticle composite having high luminescence properties, it is possible to provide a semiconductor nanoparticle composite cured film having high luminescence properties. The fluorescence quantum efficiency of the semiconductor nanoparticle composite cured film is preferably 70% or more, and more preferably 80% or more.
[0059] In order to miniaturize the device to which the semiconductor nanoparticle composite cured film is applied, the thickness of the semiconductor nanoparticle composite cured film is preferably 50 μm or less, more preferably 20 μm or less, and even more preferably 10 μm or less.
[0060] (Semiconductor nanoparticle composite patterned film and display element) The semiconductor nanoparticle composite patterned film can be obtained by forming the above-mentioned semiconductor nanoparticle composite composition or dilution composition into a film pattern. The method for forming the semiconductor nanoparticle composite composition and dilution composition into a pattern is not particularly limited, and examples thereof include spin coating, bar coating, inkjet, screen printing, and photolithography. The display element uses the semiconductor nanoparticle composite patterned film. For example, by using the semiconductor nanoparticle composite patterned film as a wavelength conversion layer, a display element having excellent fluorescent quantum efficiency can be provided.
[0061] The semiconductor nanoparticle composite of the present invention has the following configuration. (1) A semiconductor nanoparticle composite in which two or more ligands, including ligand I and ligand II, are coordinated to the surface of a semiconductor nanoparticle, The ligand comprises an organic group and a coordinating group, The ligand I has one mercapto group as the coordinating group, The ligand II has at least two mercapto groups as the coordinating groups. Semiconductor nanoparticle composites. (2) the mass ratio of the ligand I to the ligand II (ligand I / ligand II) is 0.2 to 1.5; The semiconductor nanoparticle composite according to (1) above. (3) the mass ratio of the ligand to the semiconductor nanoparticles (ligand / semiconductor nanoparticles) is 0.60 or less; The semiconductor nanoparticle composite according to (1) or (2) above. (4) the mass ratio of the ligand to the semiconductor nanoparticles (ligand / semiconductor nanoparticles) is 0.35 or less; The semiconductor nanoparticle composite according to any one of (1) to (3) above. (5) The molecular weight of the ligand is 600 or less. The semiconductor nanoparticle composite according to any one of (1) to (4) above. (6) The molecular weight of the ligand is 450 or less. The semiconductor nanoparticle composite according to any one of (1) to (5) above. (7) The total mass fraction of the ligand I and the ligand II in the ligand is 0.7 or more. The semiconductor nanoparticle composite according to any one of (1) to (6) above. (8) Each mercapto group of the ligand II is connected via 5 or less carbon atoms; The semiconductor nanoparticle composite according to any one of (1) to (7) above. (9) Each mercapto group of the ligand II is connected via three or less carbon atoms; The semiconductor nanoparticle composite according to any one of (1) to (8) above. (10) The organic group of the ligand II is a divalent or higher hydrocarbon group which may have a substituent or a heteroatom. The semiconductor nanoparticle composite according to any one of (1) to (9) above. (11) The organic group of the ligand I is a monovalent hydrocarbon group which may have a substituent or a heteroatom. The semiconductor nanoparticle composite according to any one of (1) to (10) above. (12) The ligand I is an alkylthiol; The semiconductor nanoparticle composite according to any one of (1) to (11) above. (13) The ligand I is a thiol having an alkyl group having 6 to 14 carbon atoms. The semiconductor nanoparticle composite according to any one of (1) to (12) above. (14) The ligand I is at least one selected from the group consisting of hexanethiol, octanethiol, decanethiol, and dodecanethiol. The semiconductor nanoparticle composite according to any one of (1) to (13) above. (15) The semiconductor nanoparticle composite is dispersible in at least one of hexane, acetone, PGMEA, PGME, IBOA, ethanol, methanol, and a mixture thereof, and is dispersible so that the mass fraction of the semiconductor nanoparticles is 25 mass% or more. The semiconductor nanoparticle composite according to any one of (1) to (14) above. (16) The semiconductor nanoparticle composite is dispersible in at least one of hexane, acetone, PGMEA, PGME, IBOA, ethanol, methanol, and a mixture thereof, and is dispersible so that the mass fraction of the semiconductor nanoparticles is 35 mass% or more. The semiconductor nanoparticle composite according to any one of (1) to (15) above. (17) The semiconductor nanoparticle composite has a fluorescence quantum efficiency of 70% or more. The semiconductor nanoparticle composite according to any one of (1) to (16) above. (18) The half width of the emission spectrum of the semiconductor nanoparticle composite is 40 nm or less. The semiconductor nanoparticle composite according to any one of (1) to (17) above. (19) The semiconductor nanoparticles contain In and P. The semiconductor nanoparticle composite according to any one of (1) to (18) above. (20) The composition of the surface of the semiconductor nanoparticles contains Zn. The semiconductor nanoparticle composite according to any one of (1) to (19) above. (21) When the semiconductor nanoparticle composite is heated in air at 180° C. for 5 hours, the rate of change in fluorescence quantum efficiency between before and after heating is 10% or less. The semiconductor nanoparticle composite according to any one of (1) to (20) above.
[0062] The semiconductor nanoparticle composite composition of the present invention has the following configuration. (22) A semiconductor nanoparticle composite composition in which the semiconductor nanoparticle composite according to any one of (1) to (21) above is dispersed in a dispersion medium, The dispersion medium is a monomer or a prepolymer. Semiconductor nanoparticle composite compositions.
[0063] The semiconductor nanoparticle composite cured film of the present invention has the following configuration. (23) A semiconductor nanoparticle composite cured film in which the semiconductor nanoparticle composite according to any one of (1) to (21) above is dispersed in a polymer matrix.
[0064] The semiconductor nanoparticle composite dispersion of the present invention has the following configuration. <1> A dispersion in which a semiconductor nanoparticle composite in which two or more types of ligands are coordinated to the surface of a semiconductor nanoparticle is dispersed in a dispersion medium, The ligands include ligand I and ligand II each of which is composed of an organic group and a coordinating group; The ligand I has one mercapto group as the coordinating group, The ligand II has at least two mercapto groups as the coordinating groups. Semiconductor nanoparticle composite dispersion. <2> The dispersion medium is an organic dispersion medium. the above <1> The semiconductor nanoparticle composite dispersion liquid according to claim 1. <3> the mass ratio of the ligand I to the ligand II (ligand I / ligand II) is 0.2 to 1.5; the above <1> or <2> The semiconductor nanoparticle composite dispersion liquid according to claim 1. <4> a mass ratio of the ligand to the semiconductor nanoparticles (ligand / semiconductor nanoparticles) is 0.60 or less; the above <1> ~ <3> The semiconductor nanoparticle composite dispersion liquid according to any one of claims 1 to 5. <5> a mass ratio of the ligand to the semiconductor nanoparticles (ligand / semiconductor nanoparticles) is 0.35 or less; the above <1> ~ <4> The semiconductor nanoparticle composite dispersion liquid according to any one of claims 1 to 5. <6> the total mass fraction of the ligand I and the ligand II in the ligand is 0.7 or more; the above <1> ~ <5> The semiconductor nanoparticle composite dispersion liquid according to any one of claims 1 to 5. <7> Each mercapto group of the ligand II is separated by 5 or less carbon atoms. the above <1> ~ <6> The semiconductor nanoparticle composite dispersion liquid according to any one of claims 1 to 5. <8> Each mercapto group of the ligand II is separated by no more than three carbon atoms. the above <1> ~ <7> The semiconductor nanoparticle composite dispersion liquid according to any one of claims 1 to 5. <9> The organic group of the ligand II is a divalent or higher hydrocarbon group which may have a substituent or a heteroatom. the above <1> ~ <8> The semiconductor nanoparticle composite dispersion liquid according to any one of claims 1 to 5. <10> The organic group of the ligand I is a monovalent hydrocarbon group which may have a substituent or a heteroatom. the above <1> ~ <9> The semiconductor nanoparticle composite dispersion liquid according to any one of claims 1 to 5. <11> The molecular weight of the ligand is 600 or less. the above <1> ~ <10> The semiconductor nanoparticle composite dispersion liquid according to any one of claims 1 to 5. <12> The molecular weight of the ligand is 450 or less. the above <1> ~ <11> The semiconductor nanoparticle composite dispersion liquid according to any one of claims 1 to 5. <13> said ligand I being an alkylthiol; the above <1> ~ <12> The semiconductor nanoparticle composite dispersion liquid according to any one of claims 1 to 5. <14> The ligand I is a thiol having an alkyl group having 6 to 14 carbon atoms. the above <1> ~ <13> The semiconductor nanoparticle composite dispersion liquid according to any one of claims 1 to 5. <15> The ligand I is at least one selected from the group consisting of hexanethiol, octanethiol, decanethiol, and dodecanethiol. the above <1> ~ <14> The semiconductor nanoparticle composite dispersion liquid according to any one of claims 1 to 5. <16> the organic group of the ligand II is an aliphatic hydrocarbon group having 5 or less carbon atoms; the above <1> ~ <15> The semiconductor nanoparticle composite dispersion liquid according to any one of claims 1 to 5. <17> the organic group of the ligand II is an aliphatic hydrocarbon group having 3 or less carbon atoms; the above <1> ~ <16> The semiconductor nanoparticle composite dispersion liquid according to any one of claims 1 to 5. <18> The dispersion medium is one or more mixed dispersion media selected from the group consisting of aliphatic hydrocarbons, alcohols, ketones, esters, glycol ethers, glycol ether esters, aromatic hydrocarbons, and alkyl halides. the above <1> ~ <17> The semiconductor nanoparticle composite dispersion liquid according to any one of claims 1 to 5. <19> The dispersion medium is hexane, octane, acetone, PGMEA, PGME, IBOA, ethanol, methanol or a mixture thereof; the above <1> ~ <18> The semiconductor nanoparticle composite dispersion liquid according to any one of claims 1 to 5. <20> The semiconductor nanoparticle composite has a fluorescence quantum efficiency of 70% or more. the above <1> ~ <19> The semiconductor nanoparticle composite dispersion liquid according to any one of claims 1 to 5. <21> The half width of the emission spectrum of the semiconductor nanoparticle composite is 40 nm or less. the above <1> ~ <20> The semiconductor nanoparticle composite dispersion liquid according to any one of claims 1 to 5. <22> The semiconductor nanoparticles include In and P. the above <1> ~ <21> The semiconductor nanoparticle composite dispersion liquid according to any one of claims 1 to 5. <23> The composition of the surface of the semiconductor nanoparticles contains Zn. the above <1> ~ <22> The semiconductor nanoparticle composite dispersion liquid according to any one of claims 1 to 5. <24> The mass fraction of the semiconductor nanoparticles in the semiconductor nanoparticle composite dispersion liquid is 25 mass% or more. the above <1> ~ <23> The semiconductor nanoparticle composite dispersion liquid according to any one of claims 1 to 5. <25> The mass fraction of the semiconductor nanoparticles in the semiconductor nanoparticle composite dispersion liquid is 35 mass% or more. the above <1> ~ <24> The semiconductor nanoparticle composite dispersion liquid according to any one of claims 1 to 5. <26> When the semiconductor nanoparticle composite is heated in air at 180° C. for 5 hours, the rate of change in fluorescence quantum efficiency between before and after heating is 10% or less. the above <1> ~ <25> The semiconductor nanoparticle composite dispersion liquid according to any one of claims 1 to 5. <27> The organic dispersion medium is a monomer or a prepolymer. the above <1> ~ <26> The semiconductor nanoparticle composite dispersion liquid according to any one of claims 1 to 5.
[0065] The method for producing a semiconductor nanoparticle composite composition of the present invention employs the following configuration. <28> 1. A method for producing a semiconductor nanoparticle composite composition, comprising: the above <1> ~ <27> Adding either or both of a crosslinker and a dispersion medium to the semiconductor nanoparticle composite dispersion liquid according to any one of the above items. Method for making semiconductor nanoparticle composite compositions.
[0066] The method for producing a semiconductor nanoparticle composite cured film of the present invention employs the following configuration. <29> A method for producing a semiconductor nanoparticle composite cured film, comprising the steps of: the above <28> curing the semiconductor nanoparticle composite composition obtained by the method for producing a semiconductor nanoparticle composite composition according to claim 1; Method for producing a semiconductor nanoparticle composite cured film.
[0067] It will be understood that the structures and / or methods described herein are presented as examples, and that numerous variations are possible, and that these specific examples or examples should not be taken in a limiting sense. A particular procedure or method described herein may represent one of many process methods. Thus, various acts illustrated and / or described may be performed in the order illustrated and / or described, or may be omitted. Similarly, the order of the methods described above may be altered. The subject matter of the present disclosure includes all novel and non-obvious combinations and subcombinations of the various methods, systems, and structures disclosed herein, as well as other features, functions, acts, and / or properties, and all equivalents thereof. EXAMPLES
[0068] EXAMPLES The present invention will be specifically described below with reference to examples and comparative examples, but the present invention is not limited to these. [Example 1] According to the following method, semiconductor nanoparticles were synthesized, and further, semiconductor nanoparticle composites were synthesized using the semiconductor nanoparticles. (Synthesis of semiconductor nanoparticles) -Preparation of precursor- --Preparation of Zn precursor solution-- 40 mmol of zinc oleate was mixed with 75 mL of octadecene and heated at 110° C. for 1 hour under vacuum to prepare a Zn precursor with [Zn]=0.4 M. --Preparation of Se precursor (trioctylphosphine selenide)-- 22 mmol of selenium powder and 10 mL of trioctylphosphine were mixed in nitrogen and stirred until completely dissolved to obtain trioctylphosphine selenide with [Se] = 2.2 M. --Preparation of S precursor (trioctylphosphine sulfide)-- 22 mmol of sulfur powder and 10 mL of trioctylphosphine were mixed in nitrogen and stirred until completely dissolved to obtain trioctylphosphine sulfide ([S] = 2.2 M). -Core synthesis- Indium acetate (0.3 mmol) and zinc oleate (0.6 mmol) were added to a mixture of oleic acid (0.9 mmol), 1-dodecanethiol (0.1 mmol) and octadecene (10 mL), and the mixture was heated to about 120°C under vacuum (<20 Pa) and reacted for 1 hour. The mixture reacted in vacuum was placed under a nitrogen atmosphere at 25°C, tris(trimethylsilyl)phosphine (0.2 mmol) was added, and the mixture was heated to about 300°C and reacted for 10 minutes. The reaction solution was cooled to 25°C, octanoic acid chloride (0.45 mmol) was poured in, and the mixture was heated at about 250°C for 30 minutes, and then cooled to 25°C. -Shell synthesis- After that, the mixture was heated to 200°C, 0.75 mL of Zn precursor solution and 0.3 mmol of trioctylphosphine selenide were added at the same time, and the mixture was reacted for 30 minutes to form a ZnSe shell on the surface of the InP-based semiconductor nanoparticles.Furthermore, 1.5 mL of Zn precursor solution and 0.6 mmol of trioctylphosphine sulfide were added, and the mixture was heated to 250°C and reacted for 1 hour to form a ZnS shell. -Cleaning process- The reaction solution of the semiconductor nanoparticles obtained by the above synthesis was added to acetone, mixed thoroughly, and then centrifuged. The centrifugal acceleration was set to 4000G. The precipitate was collected, and normal hexane was added to the precipitate to prepare a dispersion liquid. This operation was repeated several times to obtain purified semiconductor nanoparticles. (Synthesis of semiconductor nanoparticle composites) In preparing the semiconductor nanoparticle composite, first, the ligand was synthesized as follows. -Synthesis of dodecanedithiol- 15g of 1,2-decanediol and 28.7mL of triethylamine were placed in a flask and dissolved in 120mL of THF (tetrahydrofuran). The solution was cooled to 0°C, and 16mL of methanesulfonic acid chloride was gradually added dropwise under a nitrogen atmosphere, while being careful not to raise the temperature of the reaction solution above 5°C due to the heat of reaction. The reaction solution was then warmed to room temperature and stirred for 2 hours. The solution was extracted with a chloroform-water system, and the organic phase was recovered. The resulting solution was concentrated by evaporation, and an oily intermediate was obtained with magnesium sulfate. This was transferred to another flask, and 100mL of 1.3M thiourea dioxane solution was added under a nitrogen atmosphere. The solution was refluxed for 2 hours, after which 3.3g of NaOH was added and refluxed for another 1.5 hours. The reaction solution was cooled to room temperature, and 1M HCl aqueous solution was added until pH=7, for neutralization. The resulting solution was extracted with a chloroform-water system to obtain dodecanedithiol (DDD). -Preparation of semiconductor nanoparticle composites- The purified semiconductor nanoparticles were dispersed in 1-octadecene in a flask to a mass ratio of 20% to prepare a semiconductor nanoparticle 1-octadecene dispersion. 0.8 g of dodecanethiol (DDT) was added to 5.0 g of the prepared semiconductor nanoparticle 1-octadecene dispersion, and 3.2 g of (2,3-dimercaptopropyl)propionate was added. The mixture was stirred at 110°C for 60 minutes in a nitrogen atmosphere and cooled to 25°C to obtain a reaction solution of semiconductor nanoparticle composites. -Cleaning process- 5.0 mL of toluene was added to the reaction solution to prepare a dispersion. 25 mL of ethanol and 25 mL of methanol were added to the resulting dispersion, and the mixture was centrifuged at 4000 G for 20 minutes. After centrifugation, the clear supernatant was removed and the precipitate was collected. This operation was repeated several times to obtain a purified semiconductor nanoparticle composite.
[0069] (Optical properties / heat resistance) The optical properties of the semiconductor nanoparticle composite were measured using a fluorescence quantum efficiency measurement system (QE-2100, manufactured by Otsuka Electronics). The obtained semiconductor nanoparticle composite was dispersed in a dispersion liquid, and a single light of 450 nm was applied as excitation light to obtain an emission spectrum. The fluorescence quantum efficiency (QY) and full width at half maximum (FWHM) were calculated from the emission spectrum after re-excitation correction, which was obtained by removing the re-excitation fluorescence emission spectrum of the fluorescence emitted by re-excitation from the obtained emission spectrum. PGMEA was used as the dispersion medium. Note that normal hexane was used as the dispersion medium for the semiconductor nanoparticle composite that was not dispersed in PGMEA. The heat resistance of the semiconductor nanoparticle composite was evaluated using a dry powder. The solvent was removed from the purified semiconductor nanoparticle composite, and the dry powder was heated in air at 180°C for 5 hours. After the heat treatment, the semiconductor nanoparticle composite was redispersed in a dispersion liquid, and the re-excitation corrected fluorescence quantum efficiency (=QYb) was measured. The fluorescence quantum efficiency of the semiconductor nanoparticle composite before heating was designated as (QYa), and the heat resistance was calculated according to the following (Equation 3). (Formula 3): (QYb / QYa)×100
[0070] (Semiconductor nanoparticle composite dispersion) The purified semiconductor nanoparticle composite was heated to 550°C by differential thermogravimetry (DTA-TG), held at that temperature for 5 minutes, and then cooled. The residual mass after analysis was taken as the mass of the semiconductor nanoparticles, and the mass ratio of the semiconductor nanoparticles in the semiconductor nanoparticle composite was confirmed from this value. Based on the above mass ratio, IBOA was added to the semiconductor nanoparticle composite. The amount of IBOA added was changed, and the semiconductor nanoparticles in the dispersion were changed in 5 mass% increments from 50 mass% to 10 mass% in mass conversion, and the dispersion state was confirmed. The mass fraction at which precipitation and turbidity were no longer observed is shown in the table as the mass fraction of the semiconductor nanoparticles. In Table 2, various organic dispersion media were added to the semiconductor nanoparticle composite so that the mass fraction of the semiconductor nanoparticles was 5 mass%, and those that were dispersed at that time are indicated with an "O" and those in which precipitation or turbidity was observed are indicated with an "X."
[0071] [Example 2] The semiconductor nanoparticle composite and the semiconductor nanoparticle composite dispersion were prepared and their characteristics were evaluated in the same manner as in Example 1, except that the amount of dodecanethiol added was 1.6 g and the amount of (2,3-dimercaptopropyl)propionate added was 2.4 g when preparing the semiconductor nanoparticle composite.
[0072] [Example 3] The semiconductor nanoparticle composite was produced and its characteristics evaluated in the same manner as in Example 1, except that the amount of dodecanethiol added was 2.4 g and the amount of (2,3-dimercaptopropyl)propionate added was 1.6 g.
[0073] [Example 4] The semiconductor nanoparticle composite and the semiconductor nanoparticle composite dispersion were prepared and their characteristics were evaluated in the same manner as in Example 1, except that when preparing the semiconductor nanoparticle composite, the amount of dodecanethiol added was 1.6 g, and 2.4 g of methyl dihydrolipoate was used instead of (2,3-dimercaptopropyl)propionate. Methyl dihydrolipoate was synthesized in the following manner. -Synthesis of methyl dihydrolipoate- 2.1 g (10 mmol) of dihydrolipoic acid was dissolved in 20 mL (49 mmol) of methanol, and 0.2 mL of concentrated sulfuric acid was added. The solution was refluxed for 1 hour under a nitrogen atmosphere. The reaction solution was diluted with chloroform, and the solution was extracted in turn with a 10% aqueous HCl solution, a 10% aqueous Na2CO3 solution, and a saturated aqueous NaCl solution to recover the organic phase. The organic phase was concentrated by evaporation and purified by column chromatography using a hexane-ethyl acetate mixed solvent as the developing solvent to obtain methyl dihydrolipoate.
[0074] [Example 5] When preparing the semiconductor nanoparticle composite, the amount of dodecanethiol added was 0.6 g, the amount of (2,3-dimercaptopropyl)propionate was 2.4 g, and 1.0 g of oleic acid was added. In the same manner as in Example 1, except that, a semiconductor nanoparticle composite and a semiconductor nanoparticle composite dispersion were prepared and their characteristics were evaluated.
[0075] [Example 6] When preparing the semiconductor nanoparticle composite, the amount of dodecanethiol added was 0.4 g, the amount of (2,3-dimercaptopropyl)propionate was 2.0 g, and 1.6 g of oleic acid was added. In the same manner as in Example 1, except that, a semiconductor nanoparticle composite and a semiconductor nanoparticle composite dispersion were prepared and their characteristics were evaluated.
[0076] [Example 7] When preparing the semiconductor nanoparticle composite, the dodecanethiol added was N-tetradecanoyl-N-(2-mercaptoethyl)tetradecanamide in an amount of 1.6 g, and further, the amount of (2,3-dimercaptopropyl)propionate was 2.4 g. The same procedures as in Example 1 were repeated, except that the semiconductor nanoparticle composite and the semiconductor nanoparticle composite dispersion were prepared and their characteristics were evaluated. N-Tetradecanoyl-N-(2-mercaptoethyl)tetradecaneamide was synthesized as follows. - Synthesis of N-tetradecanoyl-N-(2-mercaptoethyl)tetradecaneamide - 0.78g (10mmol) of 2-aminoethanethiol and 3.4mL (24mmol) were placed in a 100mL round-bottom flask and dissolved in 30mL of dehydrated dichloromethane. The solution was cooled to 0℃, and 5.4mL (20mmol) of tetradecanoyl chloride was slowly added dropwise under a nitrogen atmosphere, taking care not to raise the temperature of the solution above 5℃. After the addition was completed, the reaction solution was warmed to room temperature and stirred for 2 hours. The reaction solution was filtered, and the filtrate was diluted with chloroform. The solution was extracted with 10% HCl aqueous solution, 10% Na2CO3 aqueous solution, and saturated NaCl aqueous solution in that order, and the organic phase was recovered. The organic phase was concentrated by evaporation, and then purified by column chromatography using a hexane-ethyl acetate mixed solvent as the developing solvent, to obtain N-tetradecanoyl-N-(2-mercaptoethyl)tetradecaneamide.
[0077] [Example 8] When preparing the semiconductor nanoparticle composite, the amount of dodecanethiol added was changed to 1.6 g, and (2,3-dimercaptopropyl)propionate was changed to N,N-didecyl-6,8-disulfanyloctanamide in an amount of 2.4 g. The same procedures as in Example 1 were repeated, except that the amount of dodecanethiol added was changed to 1.6 g, and (2,3-dimercaptopropyl)propionate was changed to N,N-didecyl-6,8-disulfanyloctanamide in an amount of 2.4 g. A semiconductor nanoparticle composite and a semiconductor nanoparticle composite dispersion were prepared and their characteristics were evaluated. N,N-didecyl-6,8-disulfanyloctanamide was synthesized as follows. - Synthesis of N,N-didecyl-6,8-disulfanyloctanamide - 3.0g (10mmol) of didecylamine, 1.3g (10mmol) of 1-hydroxybenzotriazole and 1.9g (10mmol) of 1-ethyl-3-(3-dimethylaminopropyl)carbodiimide hydrochloride were placed in a round-bottom flask and dissolved in 30mL of dehydrated dichloromethane. 2.1g (10mmol) of dihydrolipoic acid was added thereto and stirred at room temperature for 1 hour. The reaction solution was diluted with 100mL of dichloromethane, and extracted in the order of 10% HCl aqueous solution, 10% Na2CO3 aqueous solution, and saturated NaCl aqueous solution to recover the organic phase. The organic phase was concentrated by evaporation and then purified by column chromatography using a hexane-ethyl acetate mixed solvent as the developing solvent to obtain N,N-didecyl-6,8-disulfanyloctanamide.
[0078] [Example 9] The semiconductor nanoparticle composite and the semiconductor nanoparticle composite dispersion were prepared and their characteristics were evaluated in the same manner as in Example 1, except that the amount of dodecanethiol added was 3.2 g and the amount of (2,3-dimercaptopropyl)propionate added was 0.8 g.
[0079] [Example 10] The semiconductor nanoparticle composite and the semiconductor nanoparticle composite dispersion were prepared and their characteristics were evaluated in the same manner as in Example 1, except that the amount of dodecanethiol added was 0.4 g and the amount of (2,3-dimercaptopropyl)propionate added was 3.6 g when preparing the semiconductor nanoparticle composite.
[0080] [Example 11] When preparing the semiconductor nanoparticle composite, the semiconductor nanoparticle composite and the semiconductor nanoparticle composite dispersion were prepared and their characteristics were evaluated in the same manner as in Example 1, except that the only ligand added was dodecanethiol, and the amount of dodecanethiol was 4.0 g.
[0081] [Example 12] When preparing the semiconductor nanoparticle composite, the only ligand added was (2,3-dimercaptopropyl)propionate, and the amount of this ligand was 1.6 g. The same procedure as in Example 1 was repeated to prepare the semiconductor nanoparticle composite and to evaluate its characteristics.
[0082] [Example 13] The semiconductor nanoparticle composite and the semiconductor nanoparticle composite dispersion were prepared and their characteristics were evaluated in the same manner as in Example 1, except that when preparing the semiconductor nanoparticle composite, the amount of dodecanethiol added was 1.6 g, and (2,3-dimercaptopropyl)propionate was changed to dodecenylsuccinic acid in an amount of 2.4 g.
[0083] [Example 14] During the preparation of the semiconductor nanoparticle composite, the dodecanethiol added was changed to oleic acid in an amount of 1.6 g, and further, the amount of (2,3-dimercaptopropyl)propionate was changed to 2.4 g. The same procedures as in Example 1 were repeated, except that a semiconductor nanoparticle composite and a semiconductor nanoparticle composite dispersion were prepared and their characteristics were evaluated.
[0084] [Example 15] The semiconductor nanoparticle composite and the semiconductor nanoparticle composite dispersion were prepared and their characteristics were evaluated in the same manner as in Example 1, except that when preparing the semiconductor nanoparticle composite, the dodecanethiol added was changed to oleic acid in an amount of 1.6 g, and further, the (2,3-dimercaptopropyl)propionate was changed to dodecenylsuccinic acid in an amount of 2.4 g.
[0085] [Example 16] The semiconductor nanoparticle composite and the semiconductor nanoparticle composite dispersion were prepared and their characteristics were evaluated in the same manner as in Example 1, except that when preparing the semiconductor nanoparticle composite, the amount of dodecanethiol added was 2.0 g, and oleic acid was used instead of (2,3-dimercaptopropyl)propionate in an amount of 2.0 g. [Example 17] The semiconductor nanoparticle composite and the semiconductor nanoparticle composite dispersion were prepared and their characteristics were evaluated in the same manner as in Example 1, except that when preparing the semiconductor nanoparticle composite, the dodecanethiol added was 3,6,9,12-tetraoxadecanamine, the amount of which was 2.0 g, and the amount of (2,3-dimercaptopropyl)propionate was 2.4 g.
[0086] The results of Examples 1 to 10 are summarized in Table 1-1, and the results of Examples 11 to 17 are summarized in Table 1-2. The semiconductor nanoparticle composite preferably has a fluorescence quantum efficiency of 70% or more and a heat resistance of 10% or more. The meanings of the abbreviations shown in Tables 1-1 and 1-2 are as follows: LI: Ligand I LII: Ligand II Others: Ligands other than Ligand I and Ligand II Total L: All ligands coordinated to the semiconductor nanoparticles QD: Semiconductor nanoparticles (quantum dots) DDT: Dodecanethiol
[0087] [Table 1-1]
[0088] [Table 1-2]
[0089] [Table 2]
Claims
1. A semiconductor nanoparticle composite in which two or more ligands including ligand I and ligand II are coordinated to the surface of a semiconductor nanoparticle, The ligand comprises an organic group and a coordinating group, The ligand I is a monovalent hydrocarbon group in which the organic group may have a substituent and / or a heteroatom, and has one mercapto group as the coordinating group; The ligand II has an organic group which is a divalent or higher hydrocarbon group which may have a substituent and / or a heteroatom, and has two or more mercapto groups as the coordinating groups, each mercapto group of said ligand II is connected via 5 or fewer carbon atoms; a mass ratio of the ligand to the semiconductor nanoparticles (ligand / semiconductor nanoparticles) is 0.05 or more; the total mass fraction of the ligand I and the ligand II in the ligand is 0.7 or more; the mass ratio of the ligand I to the ligand II (ligand I / ligand II) is 0.2 to 1.5; Semiconductor nanoparticle composites.
2. The mass ratio of the ligand to the semiconductor nanoparticles (ligand / semiconductor nanoparticles) is 0.60 or less, The semiconductor nanoparticle composite of claim 1 .
3. The molecular weight of the ligand is 600 or less. The semiconductor nanoparticle composite according to claim 1 or 2.
4. Each mercapto group of the ligand II is connected via no more than three carbon atoms. The semiconductor nanoparticle composite according to any one of claims 1 to 3.
5. said ligand I being an alkylthiol; The semiconductor nanoparticle composite according to any one of claims 1 to 4.
6. The semiconductor nanoparticle composite has a fluorescence quantum efficiency of 70% or more. The semiconductor nanoparticle composite according to any one of claims 1 to 5.
7. The half width of the emission spectrum of the semiconductor nanoparticle composite is 40 nm or less. The semiconductor nanoparticle composite according to any one of claims 1 to 6.
8. The semiconductor nanoparticles include In and P. The semiconductor nanoparticle composite according to any one of claims 1 to 7.
9. The composition of the surface of the semiconductor nanoparticles contains Zn. The semiconductor nanoparticle composite according to any one of claims 1 to 8.
10. When the semiconductor nanoparticle composite is heated in air at 180° C. for 5 hours, the rate of change in fluorescence quantum efficiency between before and after heating is 10% or less. The semiconductor nanoparticle composite according to any one of claims 1 to 9.
11. A semiconductor nanoparticle composite composition in which the semiconductor nanoparticle composite according to any one of claims 1 to 10 is dispersed in a dispersion medium, The dispersion medium is a monomer or a prepolymer. Semiconductor nanoparticle composite compositions.
12. A cured film of a semiconductor nanoparticle composite comprising the semiconductor nanoparticle composite according to any one of claims 1 to 10 dispersed in a polymer matrix.
Citation Information
Patent Citations
Ultrafine semiconductor particle
JP2002121549A
Nanoparticle bondable with biomolecule, and its manufacturing method
JP2009216603A
Titanium compound containing quantum dots and production method, and photoelectric conversion element using the titanium compound containing quantum dots
JP2013136498A
Fluorescent body, wavelength converting member and light-emitting device
JP2015086284A
Semiconductor nanoparticles, dispersion liquid, film, and method for producing semiconductor nanoparticles
WO2017038487A1
